Waterbirds habitat mapping using unmanned aerial vehicle in Belawan Mangrove Ecosystems, North Sumatera, Indonesia - Thoha Achmad Siddik; Fauziyah Laely Nur; Jumilawaty Erni; Marwan Mochammad Akbar (BIO Web of Conferences)
Waterbirds are ecologically dependent on wetlands. Monitoring waterbird species diversity and habitat conditions is very important to protect natural resources from threats and habitat destruction. The use of Unmanned Aerial Vehicle (UAV) technology can overcome survey constraints for preserving mangrove ecosystems, which have difficult access and take a long time. This study aims to identify waterbirds' habitat in mangrove ecosystems in the Belawan Bird Island area of Medan City using Unmanned Aerial Vehicles (UAV). This research was conducted in June-August 2022 in the Bird Island area on the coast of Medan City, North Sumatra Province, Indonesia. The method used in the observation of waterbirds is using the path method. Field surveys for vegetation analysis use the census plot method. Furthermore, aerial photo processing and Object-Based Image Analysis (OBIA) of the mapping results through UAVs are carried out. Image processing with OBIA goes through the stages of segmentation, classification, and accuracy testing. We found 4 bird species found in Burung Island, namely, Egretta garzetta, Egretta alba, Phalacrocorax sulcirostris and Bubulcus ibis. The results of mapping using UAVs obtained a mangrove forest waterbird habitat covering an area of 1,01 hectares. The results of aerial photo identification found that the number of birds in the study area was 23,454 birds with a density of about 2 birds/m2. Vegetation found on bird islands are Avicenia marina, Rhizophora apiculata, and Nypah fruticans. Waterbirds in the Belawan mangrove area are local birds. The accuracy test results of waterbirds' habitat mapping with the OBIA method obtained an overall Overall Accuracy result of 77%. We conclude that the results of UAV mapping of waterbird habitats are reliable for use as final classification results.